Synthesis of a Rigid Tetrahedral Linker with Thioether End Groups - Kretschmer, Florian; Wild, Andreas; Hager, Martin D.; Schubert, Ulrich S. (Synthesis, 2014)
The synthesis of a tetrahedral thio end-functionalized rigid oligo(p-phenylene ethynylene) (OPE) based on a convergent approach is reported.
Keywords: alkynes; cross-coupling; nanostructures